Research in an emerging Malaysian capital market: a guide to future direction - Ramadilli Mohd, Shamsher Mohamad; Hassan, Taufiq; Syed Mohamed, Mohamed Ariff (Faculty of Economics and Management, Universiti Putra Malaysia, 2007)
In this paper, a number of key findings from published research studies on the Malaysian capital markets are summarized. There are close to 70 emerging markets in the world, and the local financial and capital markets share many of the peculiarities of these emerging markets. Based on the evidence of local share market behavior, although the market is highly volatile similar in characteristic with all emerging markets, we conclude that the local share market could be grouped among the ten most liquid and orderly emerging markets in the world with a long-run return of 18% per annum and a risk-free rate of 6%. However, the local share and bond markets behave in ways that are much closer to the more developed markets. In some respects, as will be shown in this study, research evidence on the local market is similar to the findings reported of the behavior of the 30 more developed matured markets.